Welfare Impact of Asymmetric Price Transmission on Bangladesh Rice Consumers - Mohammad Chhiddikur Rahman (University of the Philippines Los Ba\~nos, 2018)
The study examined the pattern of vertical price transmission of rice market in Bangladesh. The dynamic relationship of rice prices along the supply chain was analyzed. The impact of rice price transmission on the consumer welfare was assessed. The market power along the supply chain has been measured. Based on the findings, policy has been suggested for efficient rice marketing to improve consumer welfare through reduction of market power. Monthly farm, wholesale and retail rice prices covering the period October 2005 to June 2017 were collected from the Department of Agricultural Marketing, Bangladesh. Yearly price, demand, population and income data were collected from the Bangladesh Bureau of Statistics and Bangladesh Financial Review. The co-integrating bound test under autoregressive distribution lag approach, Vartia's algorithm for welfare measure, stochastic frontier approach for market power, and descriptive statistics were applied. Results of the study indicated the presence of asymmetric relationship both in speed and magnitude among the prices at farm, wholesale, and retail levels. That is, significant asymmetric effects are both long run and short run. Empirical results suggest that processors (wholesalers/millers) enjoy a certain advantage over primary producers (farmers) and that retailers enjoy a certain advantage over processors. Moreover, final consumers are more likely to experience a decrease in their surplus from a price increase rather than to experience an increase in their surplus from a price decrease at the upstream. Although the welfare (consumer surplus) loss for each consumer due to price transmission asymmetry was very low, the aggregate welfare loss was much significant. The study also revealed that both the rice millers and wholesalers exerted a high degree of market power. The positive value of the Lerner Index confirmed that the rice market in Bangladesh was not competitive. It also indicated the existence of market influence dominated by the supply chain actors. Therefore, market power was one of the main causes of price transmission asymmetry in the rice supply chain of Bangladesh and the potential excess profit for the limited supply chain actors (millers and wholesalers) was very large. It is recommended to improve the efficiency of vertical rice market integration in Bangladesh by government assistance. Establishment of farmers' organization can enhance their negotiation power to get better price. The government can offer incentives to establish storage in the rural areas, and easy loan or input support to enable farmers toxii choose a better selling period of their product. The credit for paddy traders and rice wholesalers can reduce the procurement and controlling power of the rice millers. The existing government procurement and pricing policies (e.g., price floor and price ceiling) can be implemented at the local markets. The government can even impose the antitrust laws to foster competitive markets by controlling actions that limit competition such as mergers and acquisitions, price setting, and collusion pricing. The government can restart public purchasing and rationing systems, targeting the low-income group consumers (e.g., open market sell) in order to avoid huge fiscal costs. The establishment of a definite agency for the rice price regulation, procurement, and distributional decisions and actions is recommended for an efficient and competitive rice supply chain in Bangladesh.
Keywords: 330; APT; Rice; Market power; Mark-up; Consumer's welfare; ARDL; NARDL; Co-integration